A realist evaluation of an antenatal programme to change drinking behaviour of pregnant women. Issue 10 (October 2015) - Doi, Lawrence; Jepson, Ruth; Cheyne, Helen
Abstract Objective to use realist evaluation to describe and explain how and in what circumstances screening and alcohol brief interventions work in routine antenatal care. Design a realist evaluation incorporating systematic reviews and qualitative data. Setting NHS Lothian, which is one of the 14 Scottish health boards. Participants participants were recruited from two maternity units. In phase one, interviews were conducted with four participants responsible for policy implementation. These data were supported by two systematic reviews. In phase two, 17 pregnant women and 15 midwives participated in interviews, with a further six midwifery team leaders involved in a focus group. Findings training and resources provided to midwives as part of the programme acted as facilitating mechanisms that improved their skills and confidence to screen and deliver alcohol brief interventions. The programme elicited positive change in attitudes to drinking in pregnancy and possibly stimulated drinking behaviour change amongst pregnant women. However, the small numbers of pregnant women being identified for alcohol brief interventions meant delivery was infrequent and resulted in the programme not working as anticipated. The findings also revealed contextual issues around midwife–pregnant woman relationship and the challenges of negotiating the timing of screening and alcohol brief interventions delivery. Conclusions Drinking in pregnancy is an emotive issue, therefore delivering alcohol brief interventions at the first antenatal appointment when they are more likely to achieve the most benefits poses challenges. When training midwives to screen and deliver alcohol brief interventions, special attention is needed to improve person-centred communication skills to overcome barriers associated with discussing sensitive prenatal alcohol use and enhance early identification and delivery of alcohol brief interventions at the first antenatal appointment.